Recent advances in solar-driven evaporation systems. Issue 48 (24th November 2020) - Xu, Zhourui; Li, Zida; Jiang, Yihang; Xu, Gaixia; Zhu, Mingwei; Law, Wing-Cheung; Yong, Ken-Tye; Wang, Yanshuai; Yang, Chengbin; Dong, Biqin; Xing, Feng
Abstract : Solar-driven evaporation as a promising and sustainable approach to convert solar energy into freshwater resource is attracting huge interest in the research community. This review aims to summarize the recent advances in system designs of solar-driven evaporation devices. Abstract : Nowadays, energy and the environment have become critical issues for determining the sustainability of the Earth. Freshwater crises, as an increasingly serious global problem, pose a great threat to our economies, the environment and us. Solar-driven evaporation has emerged as a promising and sustainable approach to convert solar energy into clean water. In fact, the production of freshwater is not only governed by heat generation at the interface, but the process also relies on the coordination and cooperation of functional modules in the solar-driven evaporation system. This review begins with system designs of solar evaporators, considering thermal manipulation structures, water transportation pathways, and vapour condensation modules, which focus on improving the overall energy utilization, long-term usability, and freshwater yield. This is followed by a summary and discussions of cutting-edge solar evaporation applications and their underlying mechanisms. Finally, existing challenges and potential solutions for future applications are discussed and provided. This review aims to provide useful guidelines and references to scientists and researchers for the future development of clean water generation systems.